A STUDY ON THE IMPACT OF COOPERATIVES ON ECONOMICAL DEVELOPMENT - Yadav, Geeta (International Journal of Research -GRANTHAALAYAH, 2018)
The idea of cooperation is not new to man. It is as old as man himself. Cooperatives are an almost universal form of organization today found in practically all countries and used by people in many ways. A Co-operative is a unique form of business used by people and businesses for their mutual benefit. Cooperatives are community-based, rooted in democracy, flexible, and have participatory involvement, which makes them well suited for economic development The meaning of cooperation is that isolated and powerless individuals can, by combining with one another, achieve advantages available to the rich and the powerful so that they may advance not only materially but also morally. In other words a cooperative is a business organization that is owned by those who use its services, the control of which rests equally with all the members. It is voluntary and democratic and the moral element is as important as the material one. Furthermore, it recognizes social, educational, and community values. An economy based on one form of business organization alone is neither desirable nor possible in modern times. To justify their existence and fulfil their purpose, cooperatives must make a significant and unique contribution to solving some of the massive problems facing mankind today. This paper examines the role of cooperative societies in economic development. The aim is to investigate the ways in which cooperatives can act as agents towards economic development.